Determining the Relationship Between Yield and Yield Components in Sunflower (Helianthus annuus L.) - Kendarini, Niken; Herwati, Anik; Novansyah, Rifky Alfariz; Ardiarini, Noer Rahmi (Journal of Agriprecision & Social Impact, 2025)
Sunflower (Helianthus annuus L.) is an essential commodity with various benefits in food, health, and industry and has a high economic value. The national sunflower plants' productivity is low, so to fulfill the market demands, creating sunflower varieties with high yields has been challenge for plant breeders. This study analyzed the relationship between yield components and sunflower yield, identifying characteristics affecting productivity. Plant selection was carried out by understanding the relationship between yield components and seed yield using statistical methods: correlation, multiple regression, and path analysis. The research was conducted in Ampeldento Village, Karangploso District, Malang Regency, East Java, from March to August 2024, using 13 genotypes of F5 open pollinated generation sunflower. Plant traits observed were plant height, number, leaf length and width of leaves, stem diameter, flowering time, harvesting time, disc flower diameter, number of seeds per plant, 100 seed weight, and seed yield. The results showed that seven yield component characters closely related to seed yield, with positive and negative correlation patterns. The number of seeds per plant had the highest direct effect, while the highest indirect effect occurred in the number of seeds per plant, which was influenced by plant height, number of leaves, stem diameter, flowering time, harvest time, and 100 seed weight. These findings provided important insights for breeding strategies in selecting superior sunflower genotypes.